2023
DOI: 10.3390/jpm13121627
|View full text |Cite
|
Sign up to set email alerts
|

Novel Echocardiographic Measurements of Right Ventricular–Pulmonary Artery Coupling in Predicting the Prognosis of Precapillary Pulmonary Hypertension

Weronika Topyła-Putowska,
Michał Tomaszewski,
Agnieszka Wojtkowska
et al.

Abstract: Background: Currently, there are many parameters with proven prognostic significance in pulmonary hypertension (PH). Recently, the parameters defining right ventricular–pulmonary artery coupling (RVPAC) have gained clinical importance. In our study, we investigated the prognostic potential of previously known single echocardiographic parameters and new parameters reflecting RVPAC in patients with precapillary PH. Objective: Our study aimed to evaluate the prognostic value of selected echocardiographic paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…The results revealed that the predictive AUC of the nomogram was 0.878 (95% CI 0.809–0.948), surpassing the predictive efficacy of individual indicators, including SOFA score and Apache II score (DeLong test, p < 0.05). RV-PA uncoupling leads to the disturbance of cardiopulmonary interactions, exacerbates right ventricular dysfunction, decreases cardiac output and oxygen content, and may cause tissue hypoperfusion of small capillaries 28 . On the other hand, inflammatory factors in sepsis, such as IL-6 and lactate, act on blood vessels, triggering the formation of thrombi and constriction of small blood vessels in sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…The results revealed that the predictive AUC of the nomogram was 0.878 (95% CI 0.809–0.948), surpassing the predictive efficacy of individual indicators, including SOFA score and Apache II score (DeLong test, p < 0.05). RV-PA uncoupling leads to the disturbance of cardiopulmonary interactions, exacerbates right ventricular dysfunction, decreases cardiac output and oxygen content, and may cause tissue hypoperfusion of small capillaries 28 . On the other hand, inflammatory factors in sepsis, such as IL-6 and lactate, act on blood vessels, triggering the formation of thrombi and constriction of small blood vessels in sepsis.…”
Section: Discussionmentioning
confidence: 99%